Меч скіфського часу зі Слов’янська. Реставрація та опис - Киркач, В.А. (Археологія і давня історія України, 2021)
Опубліковано опис ходу реставрації скіфського
меча V ст. до н. е. з фондів Слов’янського краєзнавчого музею. Первинний стан його збереження, а
також температура і волога повітря при якій
експонат зберігався, привів його до консерваційно-реставраційних та переконсерваційних робіт. Меч
потрапив до нашого музею в 2017 р. і мав дуже поганий стан збереження. Поверхня мала значний корозійний наліт. На елементах руків’я та окремих
ділянках леза отворилося розшарування металу.
У статті описано меч скіфського часу та його
реставрація, а саме: стан збереження, розміри,
етапи та технологія консервації і переконсервації.
Актуальною проблемою залишається забезпечення
правильних умов зберігання археологічного заліза
у фондах музею та наявність кваліфікованих співробітників на місцях для швидкого реанімування
експонатів. Despite the fact that Scythian weapons are quite
typical, well studied and there is a large number of
published samples, each new artifact becomes an interesting
model for scientists and museum workers.
That is why the sword this paper is focused on has
received considerable attention from researchers, museum
workers and restorers.
This article describes the sword before its restoration.
The sword has a zoomorphic volute-like top with
«eyes» at the base. There is a beak or claws in the broken
contours of the volutes. There are two grooves on
the rectangular handle, as well as transverse relief
lines. At a somewhat asymmetrical triangular intersection
there is a notch in the base. The triangular blade
also has five narrow lengthwise grooves. Its length was
73.5 cm. The blade is incomplete so that the initial
length can be assumed to be about 80 cm. The entire
surface of the sword is covered with corrosion layers of
different intensity.
The article provides a step-by-step description of the
study and restoration of the sword. An X-ray examination
conducted at the E. O. Paton Electric Welding Institute
of the National Academy of Sciences of Ukraine
resulted with radioscopic and radiographic images of
the sword.
The restoration of the sword was carried out by the
artist-restorer of metal works Victor Holub, who also
fulfilled a professional inspection of the subject, reconservation,
consolidation of certain areas of the sword.
These works continued the conservation of the sword
in 2017. But after two years of exposure (since 2018),
the sword began to get damaged again. Therefore, all
cracks were again treated with an acidified solution
based on tannin. Processing was done in several steps
with 6 hours intervals. After that, all treated areas
were impregnated with a polymer solution. The surface
of the sword was covered with a layer of preservative.
Cracks and some parts of the sword were also masticated.
The article also provides recommendations for further
correct storage of the sword including a stable
temperature-humidity regime (18—20 °C, and humidity
not more than 20 %) and protection against mechanical
influences as well as some recommendations
for materials for showcases to exhibit the sword.